Agronomic pests and economic factors influencing sustainability of bananacoffee systems of western Uganda and potentials for improvement - Ragama, P.E.; Nankinga, C.; Okech, H.; Gold, C.; Wetala, P.; Asten, Piet J.A. van; Nambuye, A. (2004)
In Uganda, banana (Musa spp) and coffee (Coffea spp) form the economic base for a big population of small-scale farmers and provide environmental protection. However, their production is currently declining. The two crops are grown in association as intercrops or adjacent monocultures but little information exists on biological and socio-economic complementarities and antagonisms between them; thus complicating interventions to reverse the decline. In view of the above, Participatory Rural Appraisals (PRAs) and diagnostic studies were conducted in 2003 to: (1) Determine management practices, constraints and market effects on the production of banana and coffee, (2) Elucidate farmers’ perceptions on production and management constraints and (3) Derive hypotheses for further participatory research. The information was obtained through group and key informant interviews,discussions and farm assessments at three sites in Mbarara district, South-western Uganda. The studies showed that pests and diseases, declining soil fertility, poor management and lack of good markets are the main causes ofthe decline. Key banana pests were banana weevil and nematodes affecting local (AAA-EA) cooking and brewing types and fusarium wilt affecting exotic (ABB, AB and AAA) brewing and dessert types. Coffee suffers mainly from coffee wilt. Banana and coffee mutually benefit each other but also compete for resources. Banana provides shade and mulch for young coffee while coffee provides husks for banana nutrients and mulch at sites closer to the coffee factories. Regular application of coffee husks in banana plantations lowers the incidence of banana weevil pest and gives bigger bunches. The antagonistic aspects of the system include coffee depletion of soils and banana shading of older coffee plants. Lack of liquidity among farmers, arising from poor markets, leads to poor crop and pest management. Revamping farmers’ organizations for marketing purposes would improve farm gate prices and hence improved liquidity for reinvestment in the system.